Reuse old medicines for new therapeutic goals: are old anti-inflammatory drug effective in Parkinson’s disease? - Santos, Soraia Isabel Aguiar dos (2020)
Parkinson's disease (PD) is the second most common neurodegenerative disease of the central nervous system (CNS), which stands out for the presence of Lewy bodies with accumulation of a-synuclein in the brain's substantia nigra. The loss of dopaminergic neurons is responsible for the reduction of dopamine levels and consequent motor changes observed in this disease. The enteric nervous system (ENS) and the immune system are interconnected and are affected by the intestinal microbiota, thus constituting an area of intense investigation due to its impact on PD. The intestine is innervated by the nerve fibers of the sympathetic and parasympathetic system and, mutually, affects brain activity through the vagus nerve and the intestinal immune system. The mechanism of gastrointestinal dysfunction related to PD includes an abnormal aggregation of proteins with consequent degeneration of the ENS, destruction of the motor nucleus of the vagus nerve, responsible for controlling the parasympathetic production of the gastrointestinal tract and/or chronic inflammation. Abnormal asynuclein aggregates in the intestine can spread through the vagus nerve to the CNS, potentially contributing to the accumulation of a-synuclein in the brain. In addition, chronic intestinal inflammation can allow rapid mobilization of abnormal proteins between the intestine and the brain. In the present work, the toxicity of an anti-inflammatory drug, 5-aminosalicylic acid (5-ASA), was tested in N9 microglial cells. This drug is used for inflammatory bowel diseases, which due to the relationship between the nervous system and the immune system through the intestinal microbiota, may have an application to PD.